Eleanor Roosevelt : a life of discovery - Freedman, Russell (New York : Clarion Books, 1993)
A biography of the first wife of a president to have a public life and career of her own.
Includes bibliographical references (p. 189-191) and index.
Booklist
8.5
5-8
Newbery Honor, 1994
Newbery Medal/Honor.
Keywords: Roosevelt, Eleanor, -- 1884-1962 -- Juvenile literature; Presidents' spouses -- United States -- Biography -- Juvenile literature; Roosevelt, Eleanor, -- 1884-1962.; First ladies; Roosevelt, Eleanor, -- 1884-1962.; Presidents' spouses -- United States -- Biography